The Saatchi Gallery Your Gallery Critic's Choice Top 10 Artists - Sofokleous, Konstantina (My University, 2026)
The Saatchi Gallery Your Gallery Critic's Choice Top 10 Artists chosen by Ana Finel Honigman. Picasso famously said, ‘It took me four years to paint like Raphael, but a lifetime to paint like a child.’ With mature artistic skill, these artists’ work expresses the vim, vibrancy, energy and ease of children’s art.
Keywords: Arts and entertainment